2020
DOI: 10.3390/ijerph17186600
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Overweight and Obesity on Plantar Pressure in Children and Adolescents: A Systematic Review

Abstract: We aimed to synthesise the results of previous studies addressing the impact of overweight and obesity on plantar pressure in children and adolescents. An electronic search of scientific literature was conducted using PubMed, Cochrane and Scopus database, with keywords: “plantar pressure” AND “children” AND “obesity”; “plantar pressure” AND “adolescents” AND “obesity”, “plantar pressure” AND “children” AND “overweight”, “plantar pressure” AND “adolescents” AND “overweight”. Twenty-two articles were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
2
23
0
2
Order By: Relevance
“…Consequently, conducting health economic studies in the region gains substantial importance [ 46 ]. The lack of physical activity results in obesity; childhood obesity in turn leads to an increase in the risk of cardiovascular diseases and diabetes in adulthood, not to mention different long-term socioeconomic consequences [ 47 ]. One solution to the problem is to introduce active breaks between school lessons when students can do short but frequent physical exercises to freshen up [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, conducting health economic studies in the region gains substantial importance [ 46 ]. The lack of physical activity results in obesity; childhood obesity in turn leads to an increase in the risk of cardiovascular diseases and diabetes in adulthood, not to mention different long-term socioeconomic consequences [ 47 ]. One solution to the problem is to introduce active breaks between school lessons when students can do short but frequent physical exercises to freshen up [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors establish that an increase in BMI leads to an increase in foot morphology particularly in metatarsal and heel width, but few correlational studies have analyzed these parameters in more detail. In children and adolescents, overweight seems to have an impact on foot structures, with changes in the anatomical structures, an abnormal distribution of the plantar pressure [ 22 , 23 , 26 ]. In our study we found a strong correlation between foot width and BMI at 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, as the foot structure is in the process of development in children, childhood obesity may undermine the foot structure and foot function and further lead to the redistribution of foot loadings [ 5 , 6 , 7 , 8 ]. Previous studies investigating the effect of increased weight on the plantar pressures and foot structural changes in children have commonly been cross-sectional [ 9 , 10 , 11 , 12 ]; obese/overweight children are compared with those of normal weight, but the temporal relationship of pathologic development on foot function with the increased excessive body mass is unknown. It is necessary to figure out how the foot function gradually changes with the increased excessive body mass that is physiologically gained over time.…”
Section: Introductionmentioning
confidence: 99%